A retrospective study of deltoid ligament repair versus syndesmotic fixation in lateral malleolus fracture combined with both deltoid ligament injury and inferior tibiofibular syndesmotic disruption - Liao, Junyi; Zhang, Jinsong; Ni, Weidong; Luo, Gang (Frontiers in Surgery, 2022)
Background: To compare clinical outcomes of deltoid ligament repair versus syndesmotic fixation in lateral malleolus fracture combined with both deltoid ligament injury and inferior tibiofibular syndesmotic disruption. Methods: Patients diagnosed with lateral malleolus fracture combined with both deltoid ligament injury and inferior tibiofibular syndesmotic disruption who received open reduction and internal fixation (ORIF) were retrospectively reviewed. Seventy-nine patients were brought into the study, including 40 patients treated with lateral malleolus fracture ORIF and trans-syndesmotic fixation, and 39 patients treated with lateral malleolus fracture ORIF and deltoid ligament repair. Basic information, pre- and postoperative radiological materials were reviewed. Visual Analog Pain Scale (VAS) score, Olerud-Molander score and American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Scale were used for evaluating pain controlling and functional recovery postoperatively at different time points. Results: No complication was reported in both groups. In trans-syndesmotic fixation group, all patients received syndesmotic screws removal 6-8 weeks postoperatively. Olerud-Molander score and AOFAS Ankle-Hindfoot Scale in deltoid ligament repair group was higher than trans-syndesmotic fixation group 3 months after operation. No statistical difference was found between the 2 groups in VAS score from 1 month to 12 months postoperatively. Conclusions: Lateral malleolus fracture ORIF and deltoid ligament repair is an effective method for lateral malleolus fracture combined with both deltoid ligament injury and inferior tibiofibular syndesmotic disruption. Compared with trans-syndesmotic fixation, deltoid ligament repair holds the advantage of no need for surgical removal of inferior tibiofibular screws postoperatively.